Joining Diverse 3D Geometries in PSTM - Ziramov, Sasha; Urosevic, Milovan; Kinkela, Jai; Dzunic, Aleksandar; Penney, M. (EAGE, 2014)
Unique set of 4 overlapped 3D hard rock seismic surveys was processed jointly after successful merging. All four data sets had significant differences in design parameters so that nominal bin size, fold, source/receiver spacing, source line/receiver line interval, azimuthal and offset distribution were quite diverse. Hence the main objective became to attenuate strong footprint caused these geometrical differences. To do so we firstly utilised unique CMP binning followed by surface consistent processing and relative amplitude preservation. Excellent PSTM results were subsequently achieved by appropriate operations performed in the offset planes and by zeroing all the extrapolated migration artefacts. This comprehensive approach resulted in amplitude consistent, fully merged 3D seismic cube with continuous reflectors across entire area which made interpretation reliable and provided assistance to the drilling program.